The effects of an in-service professional development course on Acehnese science teachers’ perceived pedagogical knowledge and skills - Ong, Eng Tek (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
This study aimed to determine the effects of a four-week in-service professional development course on Acehnese science teachers’ pedagogical knowledge and skills. A triangulation mixed-methods research design was employed: The participants’ self-perceived level of pedagogical knowledge and skills in pretest-posttest, and their written responses on what they have learnt constituted the quantitative and qualitative data respectively. The participants consisted of 26 Acehnese science teachers and were selected by means of a stratified purposive sampling. The quantitative data of pretest-posttest differences were analysed using a paired samples t-test, while the qualitative data were analysed recursively to uncover emerging themes. The findings indicated that the Acehnese science teachers perceived that their pedagogical knowledge and skills have elevated as the outcome of the professional development course. The significant gains observed were further supported by the participants’ self-written responses which upon analysis, crystallized into two major themes, namely “pedagogical knowledge gained” and the “applicability of the pedagogical knowledge gained”. A reflection on the course implementation was provided; ending with some recommendations should similar course be conducted in the future.